Interleukin 16 contributes to gammaherpesvirus pathogenesis by inhibiting viral reactivation - Liu, Shuai (PLoS Pathog, 2020)
Gammaherpesviruses have evolved various strategies to take advantage of host cellular factors or signaling pathways to establish a lifelong latent infection. Like the human gammaherpesvirus Epstein-Barr virus, murine gammaherpesvirus 68 (MHV68) establishes and maintains latency in the memory B cells during infection of laboratory mice. We have previously shown that MHV68 can immortalize fetal liver-derived B cells that induce lymphomas when injected into immunodeficient mice. Here we identify interleukin 16 (IL16) as a most abundantly expressed cytokine in MHV68-immortalized B cells and show that MHV68 infection elevates IL16 expression. IL16 is not important for MHV68 lytic infection but plays a critical role in MHV68 reactivation from latency. IL16 deficiency increases MHV68 lytic gene expression in MHV68-immortalized B cells and enhances reactivation from splenic latency. Correlatively, IL16 deficiency increases the frequency of MHV68-infected plasma cells that can be attributed to enhanced MHV68 reactivation. Furthermore, similar to TPA-mediated lytic replication of Kaposi's sarcoma-associated herpesvirus, IL16 deficiency markedly induces Tyr705 STAT3 de-phosphorylation and elevates p21 expression, which can be counteracted by the tyrosine phosphatase inhibitor orthovanadate. Importantly, orthovanadate strongly blocks MHV68 lytic gene expression mediated by IL16 deficiency. These data demonstrate that virus-induced IL16 does not directly participate in MHV68 lytic replication, but rather inhibits virus reactivation to facilitate latent infection, in part through the STAT3-p21 axis.